Assessment of the application for renewal of authorisation of VevoVitall® (benzoic acid) as feed additive for weaned piglets and pigs for fattening. (13th December 2017) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: VevoVitall ® is a feed additive consisting of benzoic acid. It is currently authorised as a zootechnical additive for weaned piglets and pigs for fattening. This opinion concerns the renewal of the authorisation of benzoic acid as a zootechnical additive in feed. In 2005 and 2017, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) adopted two opinions on the safety and efficacy of VevoVitall ® as a feed additive for weaned piglets and pigs for fattening, respectively. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. Furthermore, according to the information provided in the technical dossier, no new evidence has been identified that would make the FEEDAP Panel reconsidering the previous conclusions on the safety of the additive. The Panel confirms that the additive is safe at the maximum authorised concentrations of 5, 000 and 10, 000 mg/kg feed for weaned piglets and pigs for fattening, respectively; a margin of safety cannot be determined for weaned piglets while a margin of safety of less than 1.5 is established for pigs for fattening. The use of VevoVitall ® in feeds for weaned piglets and pigs for fattening at the maximum authorised concentrations does not pose any safety concern for consumers and the environment. The use of VevoVitall ® does not pose a risk by inhalation to users and is not a skin sensitiser. The new available data confirm that the additive is a skin irritant and a severe eye irritant. A recommendation concerning the potential toluene residues in the additive has been posted.